2014
DOI: 10.7448/ias.17.1.18848
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence and high‐risk sexual behaviours among MSM repeat and first‐time testers in China: implications for HIV prevention

Abstract: IntroductionLittle is known about HIV testing, HIV infection and sexual behaviour among bathhouse patrons in China. This study aims to assess differences in HIV prevalence and high-risk sexual behaviours between repeat and first-time testers among men who have sex with men (MSM) attending bathhouse in Tianjin, China.MethodsBetween March 2011 and September 2012, a HIV voluntary counselling and testing station was established in a gay bathhouse, which provided HIV testing and conducted a survey among participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…In our Beijing urban study, we observed an HIV prevalence of 12.7%, substantially higher than the latest national estimate (7.3%), 48 and similar to the findings documented in recent studies among Chinese MSM in other metropolitan areas (12.4%–14.5%). 43,49–51 MSM had a high HIV prevalence in Beijing, confirming our mathematical projection that the HIV epidemic continues to grow in this key population. 24 Consistent with other findings, 42,5154 we found familiar risk factors among HIV-positive MSM, including younger age of sexual debut, lower educational level, never married, transient residence, more lifetime male sexual partners, ever engaging in condomless anal sex, drug use, and alcohol use before sex.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our Beijing urban study, we observed an HIV prevalence of 12.7%, substantially higher than the latest national estimate (7.3%), 48 and similar to the findings documented in recent studies among Chinese MSM in other metropolitan areas (12.4%–14.5%). 43,49–51 MSM had a high HIV prevalence in Beijing, confirming our mathematical projection that the HIV epidemic continues to grow in this key population. 24 Consistent with other findings, 42,5154 we found familiar risk factors among HIV-positive MSM, including younger age of sexual debut, lower educational level, never married, transient residence, more lifetime male sexual partners, ever engaging in condomless anal sex, drug use, and alcohol use before sex.…”
Section: Discussionsupporting
confidence: 75%
“…Some studies have found that younger age was associated with higher HIV testing rates. 43,44 A possible explanation is that younger men visit MSM venues (e.g., gay bars, bathhouses) more frequently and would be more likely to expose to venue-based VCT. 43 However, consistent with other studies, 59 we found younger MSM were less likely to ever test for HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the risk of acquiring and transmitting HIV is amplified in the presence of STIs, it is necessary for post-test counselling to address risk among those who are chronically engaging in sexual risk behaviours. 36,37 In this study, HIV test was associated with a lower risk of HIV infection (P < 0.001, AOR ¼ 0.33, 95% CI: 0.19-0.60). Balaji et al 38 found that, compared to young MSM who had their recent HIV testing in the last 12 months, those who had their recent HIV testing more than 12 months ago were more likely to be infected with HIV.…”
Section: Self-reported Stis Hiv Testing Syphilis Statusmentioning
confidence: 73%
“…Risk reduction interventions were often venue-based to reach the largest number of vulnerable men [17]. The rapid development of greater economic purchasing power and affordable technologies have resulted in 45.8 % of China's 1.3 billion person population using the Internet in 2013, the highest absolute number of users of any nation in the world [18].…”
Section: Introductionmentioning
confidence: 99%